2021
DOI: 10.1002/adsu.202100027
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Degradation of Organic Matter in the Atmosphere

Abstract: Scheme 7. Proposed photochemical reaction pathways for some prominent NACs and ONs in •NO 3 processed wood tar aerosols. Denitration due to both A) photolysis and B) •OH photooxidation are summarized. R' could be alky or hydrogen. Reproduced under the terms of a CC-BY license. [17]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 222 publications
(166 reference statements)
0
7
0
Order By: Relevance
“…BrC primarily comes from biomass burning and fossil fuel combustion, whereas the secondary sources include photochemical reactions of anthropogenic or biogenic secondary organic aerosol precursors, [209][210][211][212] and heterogenous reactions with NO x . [210][211][212][213] The complex matrices of BrC make it difficult to determine every component of BrC, but there are several representative compounds that have been proved to be BrC, such as HULIS, nitroaromatics, PAHs, and vanillin. [210][211][212]214 LACs can undergo long-range atmospheric transport (LRAT) and then deposit on the surface of snow and glaciers.…”
Section: Sources Of Lacsmentioning
confidence: 99%
“…BrC primarily comes from biomass burning and fossil fuel combustion, whereas the secondary sources include photochemical reactions of anthropogenic or biogenic secondary organic aerosol precursors, [209][210][211][212] and heterogenous reactions with NO x . [210][211][212][213] The complex matrices of BrC make it difficult to determine every component of BrC, but there are several representative compounds that have been proved to be BrC, such as HULIS, nitroaromatics, PAHs, and vanillin. [210][211][212]214 LACs can undergo long-range atmospheric transport (LRAT) and then deposit on the surface of snow and glaciers.…”
Section: Sources Of Lacsmentioning
confidence: 99%
“…OVOCs can form SVOCs and NVOCs through free-radical reactions, thus forming SOA [43]. OVOCs can also be further oxidized and decomposed into small molecules, such as alcohols, aldehydes, ketones, ethers, or acids, and finally oxidized to CO 2 [6,117]. There are three main ways by which the effects of small-molecule organic matter on atmospheric heterogeneous reactions are produced:…”
Section: Heterogeneous Reactions Of Mixedmentioning
confidence: 99%
“…Over the past several years, photochemistry has undergone a renaissance. 31 In addition, metal-based photocatalysts were involved in studies of Sharma et al 32 where magnetic spinel ferrites MFe 2 O 4 (M = Cu, Zn, Ni, and Co) were used in the photo-Fenton process which described the degradation of MB; the addition of H 2 O 2 showed that CuFe 2 O 4 has high reactivity as compared to others such as ZnFe 2 O 4 , NiFe 2 O 4 , CoFe 2 O 4 , 33 TiO 2 , ZnO, and plasmonic metals (like Ag, Au, and pt) which were also successfully employed for efficient degradation but their potential for photoredox catalysis to create novel reactivity is limited by conventional polar reactions. 34 Many efficient catalysts have been introduced by researchers in the past, but organo-photooxidative materials have been recently explored because of their oxidative properties and stability.…”
Section: Introductionmentioning
confidence: 99%